The prevention of bullying and school harassment - Bentanachs i Sànchez, Clara (2024)
Bullying and school harassments are serious situations that children can experience at any point of their developing process. Their involvement in said situations can be derived from or bring them to a decline on their psychological well-being, and thus have severe implications in both their academic as well as social life. Children’s mental health should be seriously considered by the school settings, where children spend most of their time. This study explores the different implications of mental health in bullying and school harassment situations. Teacher’s opinions regarding bullying prevention have been studied, in order to better understand how to prevent violent situations in primary school-aged children. This study focuses on the context of Catalonia.